Physiological Importance of Hydrogen Sulfide: Emerging Potent Neuroprotector and Neuromodulator - Panthi, Sandesh (Oxid Med Cell Longev, 2016)
Hydrogen sulfide (H(2)S) is an emerging neuromodulator that is considered to be a gasotransmitter similar to nitrogen oxide (NO) and carbon monoxide (CO). H(2)S exerts universal cytoprotective effects and acts as a defense mechanism in organisms ranging from bacteria to mammals. It is produced by the enzymes cystathionine β-synthase (CBS), cystathionine ϒ-lyase (CSE), 3-mercaptopyruvate sulfurtransferase (MST), and D-amino acid oxidase (DAO), which are also involved in tissue-specific biochemical pathways for H(2)S production in the human body. H(2)S exerts a wide range of pathological and physiological functions in the human body, from endocrine system and cellular longevity to hepatic protection and kidney function. Previous studies have shown that H(2)S plays important roles in peripheral nerve regeneration and degeneration and has significant value during Schwann cell dedifferentiation and proliferation but it is also associated with axonal degradation and the remyelination of Schwann cells. To date, physiological and toxic levels of H(2)S in the human body remain unclear and most of the mechanisms of action underlying the effects of H(2)S have yet to be fully elucidated. The primary purpose of this review was to provide an overview of the role of H(2)S in the human body and to describe its beneficial effects.